Mapping Urban Halal Ecosystems: Developing Authentic Spatial Learning - Ahmad Athoriq; Yuswanti Ariani Wirahayu; Ravinesh Rohit Prasad (Future Space: Studies in Geo-Education, 2025)
The rapid expansion of halal tourism transforms urban spaces into critical learning resources for Cultural Geography, yet empirical spatial data suitable for Contextual Teaching and Learning (CTL) remain scarce. This study evaluates the spatial potential of halal tourism in the urban core of Malang City, aiming to provide authentic didactic resources for fostering spatial literacy. Focusing on Klojen District as a "Living Geography Laboratory," the research utilized a purposive sampling approach to select Kauman and Kiduldalem Villages as representative study nodes. The methodology combines the ACES Model scoring to assess pedagogical readiness and Nearest Neighbor Analysis (NNA) within a GIS framework to visualize spatial patterns. The results demonstrate that Malang City possesses significant potential as an educational resource, supported by a mean ACES score of 73. Spatially, the analysis confirms a "Clustered" distribution pattern for both places of worship (T=0.08–0.1) and halal culinary outlets (T=0.10–0.4). From a geography education perspective, these findings validate the concept of Spatial Association, illustrating how cultural values (religion) dictate urban land use. The study concludes that the generated maps and spatial data serve as essential visual learning media. By analyzing these "Urban Halal Ecosystems," educators can effectively teach Spatial Thinking Skills, moving students beyond theoretical knowledge to analyzing real-world spatial interactions.